The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/olq.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Partner Services in Sexually Transmitted Disease Prevention Programs

Abstract: Background Partner services have been a mainstay of public health sexually transmitted disease (STD) prevention programs for decades. The principal goals are to interrupt transmission and reduce STD morbidity and sequelae. In this paper, we review current literature with the goal of informing STD prevention programs. Methods We searched the literature for systematic reviews. We found nine reviews published between 2005 and 2014 (covering 108 studies). The reviews varied by study inclusion criteria (e.g., stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 48 publications
(74 reference statements)
1
59
0
2
Order By: Relevance
“…17511 This demonstrates that during our current epidemic, with high levels of HIV and syphilis coinfection, syphilis case investigation is as efficient as HIV case investigation in identifying newly-diagnosed HIV infection.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…17511 This demonstrates that during our current epidemic, with high levels of HIV and syphilis coinfection, syphilis case investigation is as efficient as HIV case investigation in identifying newly-diagnosed HIV infection.…”
Section: Discussionmentioning
confidence: 86%
“…Efficiency has been quantified in many ways, 56 including as the number of treated partners per case interview, 7 likelihood and magnitude of future transmission, 4 and number of infected partners found per case. 89 More recently, calculation of the number of patients needed to interview to identify a new case of disease that is, number needed to interview (NNTI), has been used to assess the efficiency of partner investigation.…”
mentioning
confidence: 99%
“…Previous systematic reviews and meta-analyses have suggested that EPT (as well as other practical tools to support partner notification efforts) increases the likelihood of notification, thereby also increasing the probability that sexual partners will be encouraged to seek formal HIV/STI counseling and testing [3, 4, 39, 40]. However, none of these outcomes has been fully evaluated in RCTs of MSM sexual partnerships or in developing country settings.…”
Section: Introductionmentioning
confidence: 99%
“…9 Telephone interviews may be more efficient than in-person interviews; however, their relative effectiveness is uncertain. A survey of attendees of STD and community clinics as well as a community based organization about hypothetical PS found that there was no significant difference in favorability of in-clinic notification compared to telephone notification from the perspective of OPs or partners.…”
Section: Introductionmentioning
confidence: 99%